2016
DOI: 10.4236/ojms.2016.61003
|View full text |Cite
|
Sign up to set email alerts
|

Study of Bacterial Diversity of Mangroves Rhizosphere

Abstract: Microbial diversity has been an important facet of scientific research, since microbes promise a plethora of biomolecules which are otherwise not found in nature. Microbes are subjected to high level of competition for survival in the environment, and hence develop mechanisms of defense. The biomolecules produced by these microbes as part of their defense or survival mechanism, are of importance for human and animal drugs and many other industrial and environmental applications. The marine counterparts of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Many microbes are found in mangrove forests, but studies are still needed to link microbial diversity and function as well as an assessment of how environmental changes can affect microbes [25]. Microbial diversity is an important aspect to study because of its potential to produce biomolecules that can be utilized by humans [26]. Bhitarkanika mangrove soil has a diversity of bacteria which is dominated by the genera Bacillus, Pseudomonas, Desulfotomaculum, Desulfovibrio, Desulfomonas, Methylococcus, Vibrio, Micrococcus, Klebsiella and Azotobacter [27].…”
Section: Resultsmentioning
confidence: 99%
“…Many microbes are found in mangrove forests, but studies are still needed to link microbial diversity and function as well as an assessment of how environmental changes can affect microbes [25]. Microbial diversity is an important aspect to study because of its potential to produce biomolecules that can be utilized by humans [26]. Bhitarkanika mangrove soil has a diversity of bacteria which is dominated by the genera Bacillus, Pseudomonas, Desulfotomaculum, Desulfovibrio, Desulfomonas, Methylococcus, Vibrio, Micrococcus, Klebsiella and Azotobacter [27].…”
Section: Resultsmentioning
confidence: 99%
“…Despite much research in this field, the results are somewhat conflicting and confusing. For example, some use nutrient agar for the growth of total colony counts from mangrove soil (Kumar et al, 2007;Ambeng et al, 2019) while some use Tryptic Soya Agar (TSA) (Pupin and Nahas, 2014).In comparison, others preferred Zobell's marine agar (ZB agar), and synthetic seawater media (Sakhia et al, 2016;Saravanakumar et al, 2016;Schut et al, 1993). Our results suggested that the NA media is suitable for counting and isolating microbes from mangrove soil and sediments.…”
Section: Preservationmentioning
confidence: 86%
“…Bacteria is one kind of microorganisms, there are two groups of bacteria, they are archaebacteria and eubacteria (Sattley & Madigan, 2015), moreover, eubacteria/bacteria is more common and has various kind of their own group. These bacteria can also live in the soil as a decomposer, such as decomposer in mangrove soil (Chen et al, 2016;Sakhia et al, 2016;Wu et al, 2016;Ambeng et al, 2019). Recent study shows that bacteria live in mangrove soil to decompose mangrove litter and constantly live at there due to condusive environment to them for living.…”
Section: Microbiologymentioning
confidence: 99%
“…Recent study shows that bacteria live in mangrove soil to decompose mangrove litter and constantly live at there due to condusive environment to them for living. Some example mangrove bacteria are from genus Bacillus (Sakhia et al, 2016;Ambeng et al, 2019), Microccous, Yangia, Rhodococcus, Escherecia, Pseudotoromonas, Aerococcus, Pseudoteromonas (Sakhia et al, 2016), Staphylococcus, Vibrio, Alteromonas, Listeria, Macrococcus (Ambeng et al, 2019), Proteobacteria, Chloroflexi, Bacteriodetes, Planctomycetes (Wu et al, 2016). Those bacteria and mangrove soil can be potential learning sources for stundents.…”
Section: Microbiologymentioning
confidence: 99%